Psychological Combustion of Male and Female Sport Teachers At the Primary School Stage - Alhamdi, Maytham Mohsin Habeeb; Jabbar, Alaa Mohammed (International Journal of Psychosocial Rehabilitation, 2025)
The sport teachers feel that their ability to carry out the responsibilities of learning as a result of psychological pressures. Teachers feel that there is much to be done but they could not, this causes more nervous pressure on them. Teachers feel that dealing with colleagues at work or pupils causing them a lot of tension, what really annoys them of excitement and anger. The Teachers feel frustrated as a result of their entrances without the time break between lessons, and therefore increase the negative feelings toward education. The Teachers feel that their duties in education distract them from their requirements of life and thus feel completely exhausted after the end of classes. That does not include the preparation of professional teachers only, but requires the preparation of psychologically work toward their colleagues beaming light. The need for the involvement of teachers in the development of training courses on how to good management and spreading the spirit of psychological satisfaction to colleagues and support those to play will make them more functional and psychological satisfaction. It is essential to activate the role of the media and the importance of the physical and psychological health